2021
DOI: 10.1007/s10877-021-00651-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PEEP on the relationship between tidal volume and total impedance change measured via electrical impedance tomography (EIT)

Abstract: Electrical impedance tomography (EIT) is used in lung physiology monitoring. There is evidence that EIT is linearly associated with global tidal volume (VT) in clinically healthy patients where no positive end-expiratory pressure (PEEP) is applied. This linearity has not been challenged by altering lung conditions. The aim of this study was to determine the effect of PEEP on VT estimation, using EIT technology and spirometry, and observe the stability of the relationship under changing lung conditions. Twelve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…Ventilation was considerably greater in the central regions compared with the peripheral regions, and, in the right lung, the centrodorsal part always had the greatest ventilation. This finding was in agreement with EIT studies in other mammals [ 16 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Ventilation was considerably greater in the central regions compared with the peripheral regions, and, in the right lung, the centrodorsal part always had the greatest ventilation. This finding was in agreement with EIT studies in other mammals [ 16 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 93%
“…Measurements using EIT in new-born human babies also determined greater ventilation in the right lung [ 54 , 55 ]. The phenomenon that the right lung is preferentially ventilated also in adult mammals has been observed in humans, horses, and steers [ 16 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For most people with ARDS, mechanical ventilation is a mature method to maintain normal breathing of patients, but unreasonable ventilator parameters may aggravate the lung condition and even cause serious lung injury (Prost et al, 2011). Therefore, the most common protective ventilation strategy is to reduce lung injury by setting a reasonable PEEP (positive end-expiratory pressure) value (Guerin, 2011;Brabant et al, 2019). As a noninvasive medical imaging technology, EIT can monitor the air distribution of mechanical ventilation in real time by imaging the cross section of thoracic cavity (Blankman and Gommers, 2012;Andiani et al, 2019).…”
Section: Pulmonary Ventilation Monitoringmentioning
confidence: 99%
“…This makes EIT a useful tool for real-time lung function monitoring. Many studies have shown the importance of EIT for revealing vital signs related to ventilation properties, such as tidal volume (TV) [ 2 ], or pathological situations, such as acute respiratory distress syndrome (ARDS) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%